Introduction to the humanities - Sanchez, Custodia A.; Abad, Paz F.;Jao, Loreto V. (Manila, Philippines : Rex Book Store, 1998)
Humanities is applied to a realm so vast as to embrace literature, drama, and the film; the visual and the decorative arts; music and dance. Introduction to the Humanities introduces the students to the different areas of the arts giving them a knowledge of various subject areas it covers. The book will teach the arts to those who never have known it before. It will serve not only as a practical classroom textbook in humanities but also a helpful reference book for the student in art appreciation and related course. The importance of the human being, his feelings and how he expresses those feelings is emphasized... - - Preface
Part I. General Overview of Humanities -- Part II. Painting, Sculpture and Architecture -- Part III. Literature and the Drama -- Part IV. Music and Dance.
Includes bibliographical references and index.
Keywords: HUMANITIES